2022
DOI: 10.1021/acs.joc.2c00219
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Access to 2-Iminoimidazolidines via AgF-Mediated Cascade Reactions

Abstract: A convergent access to substituted 2-iminoimidazolidines from aromatic amines and N-propargyl S-methylthiourea is developed via Ag­(I)-mediated cascade guanylation–cyclization reactions. This method features high regioselectivity, excellent efficiency, and mild reaction conditions. Subsequent deprotection of the Boc (tert-butyloxycarbonyl) group under acidic conditions provides expedient access to aryl 2-aminoimidazole derivatives in a convenient manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The BINAP‐AgF complex catalyzed enantioselective protonation of silyl enol ethers [91] . AgF found also use in other types of organic reactions [91–102] . As we will see in section 3.2, AgF found also some use in certain direct fluorinations in organic chemistry.…”
Section: Properties Of Silver and Its Compoundsmentioning
confidence: 94%
See 1 more Smart Citation
“…The BINAP‐AgF complex catalyzed enantioselective protonation of silyl enol ethers [91] . AgF found also use in other types of organic reactions [91–102] . As we will see in section 3.2, AgF found also some use in certain direct fluorinations in organic chemistry.…”
Section: Properties Of Silver and Its Compoundsmentioning
confidence: 94%
“…[91] AgF found also use in other types of organic reactions. [91][92][93][94][95][96][97][98][99][100][101][102] As we will see in section 3.2, AgF found also some use in certain direct fluorinations in organic chemistry.…”
Section: Compounds Of Monovalent Silvermentioning
confidence: 99%
“…lead to a seven-membered ring. In terms of pK a , the electronwithdrawing effect of the Proc group lowers the pK a value of N3-nitrogen, 6 making it easy to initiate nucleophilic attack in the absence of a base, as previous study showed that other nitrogen of the guanidine group might be preferred when a strong base was applied. 4k Meanwhile, we also noticed exclusive formation of the E-isomer for vinyl halides.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
“…These two compounds were prepared via a procedure mentioned in the previous report. 36 To a mixture of 1,3-bis(t-butoxycarbonyl)-2-methylisothiourea (1.71−3.43 mmol, 1.0 equiv) and bromide compound (benzyl bromide or 1bromopropane, 10.0 equiv) in DCM (20 mL), 2-tert-butyl-1,1,3,3tetramethylguanidine (Barton's base, 3.0 equiv) was added, and the mixture was stirred at room temperature for 1 h. Then, it was diluted with DCM, washed with H 2 O, and the organic phase was concentrated under reduced pressure. The obtained crude product was purified by silica gel column chromatography to yield compound 2b or 2c.…”
Section: ■ Conclusionmentioning
confidence: 99%